The Relationship between Fast Food Consumption and the Incidence of Obesity in Students of SMA Negeri 3 Subang and Its Review According to Islamic Views - Fachmi Ramadani; Fathul Jannah (Junior Medical Journal, 2023)
Unhealthy and low quality food is what makes up the majority of fast food. Halal and good quality food and drinks are recommended in Islam. These foods and beverages should not only satisfy hunger but also bring health benefits to consumers in the short and long term. Consuming excess fast food can interfere with and damage health such as, the body becomes fat or obese and the emergence of various cardiovascular diseases. Researchers at SMA Negeri 3 Subang began using a quantitative cross-sectional analytic observational methodology to establish a causal relationship between their students' love of fast food and the increasing obesity rate in their school. Univariate and bivariate statistics were used to analyze the data. The results showed that the highest body mass index of SMA Negeri 3 Subang students was normal with a total of 41 (42.3%) students, while the body mass index for obesity was 19 (19.6%) students. 54 (55.7%) students of SMA Negeri 3 Subang have a habit of frequently consuming fast food, while 43 (44.3%) of other students have a habit of rarely consuming fast food. The research data showed that there was no significant relationship between fast food consumption and the incidence of obesity in SMA Negeri 3 Subang students. (p-value = 0.138). The Islamic view regarding the relationship between fast food consumption and obesity is that Islam instructs people to eat halal, thayyib and not excess food